INFLUENCE OF RELIGIOSITY ON WELL-BEING AMONG LITERATE AND ILLITERATE PERSONS - Ansari, Masaud (European Scientific Journal, ESJ, 2015)
The present investigation was intended to ascertain the influence of Religiosity on Well-being, The sample consisted of hundred Literate and hundred Illiterate participants, they were assessed by Religiosity Inventory (Deka and Broota, 1985) and Well-Being Inventory (Jagsharanbir Sing and Dr. Asha Gupta, 2001). Simple Linear Regression was applied to examine the Correlation between Religiosity and Well-being as well as influence of religiosity on well-being, whereas correlation was found to be R=.437 and R Square Change was 19.1% which represent the contribution of predictor variable in Literate group while among Illiterate group correlation was found to be R=.159 and R Square Change was found to be 2.5% which represent the actual contribution of predictor variable in Illiterate group. The correlation between Religiosity and Well-being with its five dimensions i.e. Physical, Mental, Social, Emotional and Spiritual Well-Being among Literate and Illiterate persons was studied, The findings showed that Religiosity in Literate group was found significantly correlated with Physical and Spiritual Well-Being, and others were insignificantly correlated, whereas in the Illiterate group Social Well-Being was found significantly correlated with Religiosity, and others dimensions were insignificantly correlated. Further t-test was administered where it was found that there were significant differences between Religiosity of Literate and Illiterate group as well as Well-being of both groups. Regarding implication of the study there should be provision in schools and educational systems for learning as well as awareness programs for Illiterate individuals towards literacy through which they can learn things independently in a broader way, and will not face any hurdle at any stage of their lives.